(untitled) (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2018)
Creative accounting can be described as an accounting practice that may or may not follow the accounting standards and principles. However, it deviates from the main idea of those standards and principles in order to present the desired picture of the business. Creative accounting is not illegal, but unethical since it doesn’t meet the main objective of financial reporting – to present fair and objective picture of the business. The practice of creative accounting usually includes overstating assets, high stocks, decreasing expenses, changes of depreciation methods, or presenting provisions as an asset. Creative accounting techniques follow the changes of accounting standards, which are modified in order to reduce financial information manipulation. However, such changes in accounting standards often result in new opportunities for accounting manipulation. Although entities follow the accounting standards, they also use “loopholes” to enhance key financial ratios. Therefore, it is very important to adopt measures that will prevent the abuse of creative accounting practices. The aim of the paper is to present the main motives for financial information manipulation, as well as the most common techniques, and finally the measures that have to be taken in order to minimize creative accounting practices.